PERFORMANCE IMPROVEMENT: THE PROMINENCE OF EMPLOYEE PROACTIVENESS, GROWTH MINDSET, AND PERCEIVED USEFULNESS (VALID EVIDENCE FROM PT. LITERA MEDIATAMA EMPLOYEES) - Juma'ali Davit Lestari; Yunus Handoko; Mohammad Maskan (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2025)
PT Litera Mediatama, one of the indie publishers, has successfully negotiated the difficulties posed by the COVID-19 outbreak and its aftermath. Litera Publisher is still very much committed to helping its staff perform better. Through the mediation of perceived usefulness, this research aimed to ascertain the direct and indirect impacts of proactive personality traits and growth mindset on employee performance. All full-time and part-time workers at Litera Publisher were included in the research. One hundred and fifty-five people were surveyed using an online questionnaire; the participants were chosen using a saturation sampling method, often known as a census. The quantitative data that was gathered was evaluated using PLS-SEM analysis with SmartPLS software. Through perceived usefulness as a mediating variable, the findings demonstrated that proactive personality traits and a development mindset significantly impact employee performance, both directly and indirectly. It is anticipated that a qualitative method or a formative indicator model would be considered in future study. Researchers may try it out on other publishers or recruit people from different indie publishing houses in Indonesia to verify the unbiased framework model.